Intersectoral governance for health in all policies - structures, actions and experiences - Cohn, Amélia (Revista de Direito Sanitário, 2013)
Resenha da obra "Intersectoral governance for health in all policies - structures, actions and experiences" (David V. McQueen, Matthias Wismar, Vivian Lin, Catherine M. Jones, Maggie Davies editores, WHO/ EuropeanObservatory on Health System and Policies)